Oral therapy extension programme: half yearly report, July-December 1985, phase II - BRAC (© BRAC, 2016)
1. Introduction 2. Strategies 3. Operational performance 4. Impact evaluation 5. Chloride concentration 6. IGS usage survey 7. Personnel